1998
DOI: 10.2135/cropsci1998.0011183x003800010022x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ozone Stress on Soybean Response to Carbon Dioxide Enrichment: III. Yield and Seed Quality

Abstract: Ozone in the troposphere can cause plant stress, whereas elevated CO. generally causes positive responses. Little is known of how these gases interact to affect plant response. Interactive effects on yield and seed quality of soybean [Glycine max (L.) Merr.] grown in 14-L pots were measured in open-top field chambers. Essex was tested in 1993, and Essex, Holladay, and NK 6955 were tested in 1994. Plants were exposed from emergence to maturity to four CO; levels (ambient and 1.3,1.6, and 2.0 times ambient) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
55
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 0 publications
12
55
1
1
Order By: Relevance
“…For example, oleic acid concentration increased with increasing temperatures while linoleic acid decreased (Carver et al 1986;Rennie and Tanner 1989;Rebetzke et al 1996). Heagle et al (1998) observed a positive, significant effect of CO 2 enrichment on soybean seed oil and oleic acid concentration.…”
Section: Ricementioning
confidence: 81%
See 1 more Smart Citation
“…For example, oleic acid concentration increased with increasing temperatures while linoleic acid decreased (Carver et al 1986;Rennie and Tanner 1989;Rebetzke et al 1996). Heagle et al (1998) observed a positive, significant effect of CO 2 enrichment on soybean seed oil and oleic acid concentration.…”
Section: Ricementioning
confidence: 81%
“…Phosphorus concentration in seed was also increased and 50% of this phosphorus in soybean is in phytate form. Heagle et al (1998) found a significant effect of elevated CO 2 on soybean oil in cultivars Essex, Holladay and NK6955. The oleic acid concentration was positively affected by CO 2 and the effect of cultivar was also highly significant.…”
Section: Ricementioning
confidence: 91%
“…However, the individual effects of these pollutants on crop growth and yield are not simply additive in combined exposures (Barnes & Pfirrmann, 1992 ;Mulchi et al, 1992 ;Reinert & Ho, 1995 ;Fiscus et al, 1997 ;McKee et al, 1997a ;Mulholland et al, 1997a ;Heagle et al, 1998).…”
Section: Concurrent Emissions Of Nitrogen Oxides and Volatile Organicmentioning
confidence: 99%
“…However, results of the effects of elevated CO 2 on seed composition are still conflicting. For example, small effects of elevated CO 2 on seed composition were found [40], whereas others found a significant effect of elevated CO 2 on soybean seed oil in cultivars Essex, Holladay, and NK6955 [41]. The authors also found that oleic fatty acid concentration was positively affected and protein concentration was not affected by CO 2 .…”
Section: Soybean -The Basis Of Yield Biomass and Productivitymentioning
confidence: 95%